Establishing conditions for simulating hydrophobic solutes in electric fields by molecular dynamics Effects of the long-range van der Waals treatment on the apparent particle mobility - Milicevic, Zoran; Marrink, Siewert J.; Smith, Ana-Suncana; Smith, David M. (Journal of Molecular Modeling, 2014)
Despite considerable effort over the last decade, the interactions between solutes and solvents in the presence of electric fields have not yet been fully understood. A very useful manner in which to study these systems is through the application of molecular dynamics (MD) simulations. However, a number of MD studies have shown a tremendous sensitivity of the migration rate of a hydrophobic solute to the treatment of the long range part of the van der Waals interactions. While the origin of this sensitivity was never explained, the mobility is currently regarded as an artifact of an improper simulation setup. We explain the spread in observed mobilites by performing extensive molecular dynamics simulations using the GROMACS software package on a system consisting of a model hydrophobic object (Lennard-Jones particle) immersed in water both in the presence and absence of a static electric field. We retrieve a unidirectional field-induced mobility of the hydrophobic object when the forces are simply truncated. Careful analysis of the data shows that, only in the specific case of truncated forces, a non-zero van der Waals force acts, on average, on the Lennard-Jones particle. Using the Stokes law we demonstrate that this force yields quantitative agreement with the field-induced mobility found within this setup. In contrast, when the treatment of forces is continuous, no net force is observed. In this manner, we provide a simple explanation for the previously controversial reports.
Keywords: Molecular dynamics; Electrophoretic mobility; Van der Waals interactions; GROMACS